Pause (Waqf) and Starting Point (Ibtida’), Concept, Types, Reasons for Differences among Interpreters: An Original Study - Bani Mfarej, Ahmad Abdel Qader Ahmad; Bani Melhem, Barakat Ahmad Mustafa (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This study addresses the concept of waqf (pause) and ibtida (strating) in the reciting of the holy Book "Al-Quran" and terminology, It clarifed their types and categories based on description and cause. It also discusses the distribution, differences, and variations in the meanings and concepts due to interpreter’s differences. Methods: The inductive approach was adopted by analyzing the studies of waqf and ibtida to extract its concept and types, the deductive approach to deducing the reasons for the differences among interpreters regarding the places of pause and starting in the Holy Quran. The analytical approach analyzes texts related to pauses and stops and the topics and rulings that arise from them. Results: The study included several results, the science terminology of waqf differs from the concept of waqf in reading, in terms of comprehensiveness and generality. It became clear that the science of pausing and starting is broader and more comprehensive than pausing itself in reading, while the terminology concept of waqf (pause) and ibtida (strating) in reading is more specific than the science of waqf, as it is limited to the situational aspect of application; it is closer to the linguistic meaning than to the terminological one. Conclusions: The study concluded that types of pauses and starting vary and differ due to diversity and multiplicity of their causes, revealing that there are other types of pauses and starting beyond those outlined by scientists due to the reason for the pause and strating, as it was clarified in the core of the study.